DOLOMITE USE IN THE PRODUCTION OF SINGLE PHOSPHATE FERTILIZERS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The results of studies on the use of dolomite for the neutralization of phosphoric acid are presented. It has been shown that to obtain single phosphoric fertilizers, phosphoric acid containing 1% ammonium nitrate must be neutralized with dolomite at a stoichiometric rate for the formation of monocalcium phosphate at a temperature of 60 C and a process duration of 30 minutes. After drying, phosphate fertilizers contain at least 98.58% digestible and at least 93.44% water-soluble P2O5.